Shopping for High-Technology Treatment in Another Province - Giselle Revah and Chaim Bell (ElectronicHealthcare, 2007)
In order to address long healthcare waits, political and professional groups have recommended sending patients to other provinces for diagnostic procedures or treatment. We investigated the feasibility of such recommendations, specifically, whether residence in one province can impede access to MRIs in another province. We contacted all public MRI facilities in Canada and found no difference in wait times between prospective in- and out-of-province patients, although wait times were highly variable from province to province. Over one-fifth (19/86=22%) of centres imposed barriers for out-of-province patients to access care. We discuss several jurisdictional, financial and logistic considerations regarding the feasibility and appropriateness of implementing a national strategy of interprovincial patient transfer for healthcare.
Keywords: High-Technology Treatment, wait times, accessibility, out-of-province MRI, interprovincial access